The Influence of Anxiety and Stress toward Depression in Institutionalized Elderly - Maria Manungkalit; Ni Putu Wulan Purnama Sari (Journal of Educational, Health and Community Psychology, 2020)
Due to age-related changes, the elderly are prone to psychological problems, such as anxiety and stress, and mental disorder, such as depression. This study aimed to analyze the influence of anxiety and stress on depression in elderly living in the nursing home. This cross-sectional study involved 145 elderly in a private nursing home in Surabaya, Indonesia. Hamilton Anxiety Rating Scale (HARS), Suan Prung Stress Test - 20 (SPST-20), and Geriatric Depression Scale (GDS) was used for collecting data. Linear and ordinal regression tests were used in data analysis (Î±<0.05).Â  Results showed that the majority was old married Chinese female with basic education level, and living in the nursing home for 1-3 years. Averagely, respondents had mild anxiety, mild stress, and not depressed. Anxiety has a significant influence on depression in elderly living in the nursing home (p = 0.000), and it was accounted for 12.8% variance of depression in this population (R2 = 0.128). Stress has significant influence also on depression (p = 0.000), and it was accounted for 24% variance of depression in this population (R2 = 0.240). Stress is proved to have more influence on depression in the elderly living in a nursing home compared to anxiety.Keywords: anxiety, depression, elderly, institutionalized elderly, nursing home, stress